CHALLENGING QUESTIONS IN ENVIRONMENTAL MONITORING OF GROUNDWATER QUALITY IN RURAL AREAS OF KYIV’S REGION - Сердюк, Вікторія Анатоліївна (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2020)
Water resources protection is the prioritized target all over the world. Of course, it is Ukraine’s aim too. Environmental crisis grows stronger because of global warming. Monitoring of groundwater quality and water resources assessment requires immediate improvement and a framework for monitoring should be launched as soon as possible. After all, the delays observed 10-15 years ago have shown that humanity is unable to postpone the issue of environmental crisis until the emergence of slow solutions, either the availability of funds, or any other favorable moment. Environmental crisis has already begun on a large scale. So, regions of Ukraine, which were fully provided with water, have started to suffer from drought and hurricanes. Water wells in rural areas are running dry and in some places the water disappeared completely. Kyiv’s region is not an exception. Also, it is one of the most populated regions in Ukraine. Eco-friendly water supply to Ukrainian cities is permanently much talked-of topic in public settings. At the same time, matter of villages survival is suppressed. Taking into account disproportionate distribution of water resources between rural community and citizens, financial component becomes considerably important. Forasmuch as water is supplied for more financially reliable big-city residents for tens or even hundreds of kilometers from the location of a city. Therefore, the area that would have used these resources (most commonly it is rural area) is losing them. Approaches to solution of this problem should be overviewed and water monitoring should be actively started. Also causes of pollution of existing drinking water should be identified and removed. It is imperative to act in a goal-directed manner and to found a group of researchers and advance into action. Underground water massif should be examined as complex system (supersystem) of drinking water supply of population with the goal of improvement of current monitoring system. At the legal level there are all opportunities for implementation of the research of this system and first steps of state monitoring implementation has been done. Although it is not enough. As mathematically sound calculations show, value of this work operation and involvement of human resources could not be higher than service fee of safe environment and investments into health of rural population.